High-strength and high-plasticity martensite Ti-Al-Zr-Cr-Cu titanium alloy and preparation method

By introducing Cu into martensitic titanium alloys to construct an orthorhombic martensite structure and performing thermomechanical processing and aging treatment, the problems of insufficient strength and temper brittleness in martensitic titanium alloys are solved, achieving a good match of high strength, high plasticity and corrosion resistance, making it suitable for aerospace, weaponry, petrochemical and other fields.

CN121023299APending Publication Date: 2025-11-28XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511176084.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

In the prior art, titanium alloys have problems with high strength and ductility, similar to martensitic titanium alloys. These problems include insufficient strength and significant "temper brittleness," which are characteristic of martensitic titanium alloys, representing a strength-ductility inversion problem.

Method used

By introducing Cu to adjust phase stability and constructing an orthorhombic martensite structure, the high work hardening, grain refinement, and increased phase interface density brought about by martensitic phase transformation are utilized. Combined with thermomechanical processing and aging treatment, and by controlling the cooling rate and medium quenching, nanoscale Ti2Cu particles are formed, thereby achieving a synergistic improvement in the strength and plasticity of martensitic titanium alloys.

Benefits of technology

It achieves a good match of ultra-high yield strength, high tensile plasticity and high work hardening ability. The alloy has excellent corrosion resistance and high specific strength, and is suitable for a wide range of industrial fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121023299A_ABST
    Figure CN121023299A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-plasticity martensite Ti-Al-Zr-Cr-Cu titanium alloy and a preparation method, and belongs to the technical field of high-performance alloy materials, the titanium alloy comprises, by mass, about 5.2% of Al, 4.5% of Zr, 2.8% of Cr, 2% of Cu, and the balance Ti and inevitable impurity elements. In the preparation process of the titanium alloy, a large number of dislocations generated in the hot machining (hot rolling) process are utilized, dense coherent nanometer martensite is mediated to be formed through rapid water cooling and oil cooling processes, martensite partial decomposition and nanometer intermetallic compound Ti2Cu precipitation are induced through simple aging treatment, and the titanium alloy is obtained. And more interfaces are introduced to hinder dislocation free sliding, so that the strength and plasticity of the alloy are synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-performance alloy materials technology, specifically a high-strength and high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy and its preparation method. Background Technology

[0002] Titanium alloys possess excellent comprehensive properties, including low density, high specific strength, high specific stiffness, corrosion resistance, and higher creep strength. These properties enable them to meet the design requirements of lightweight, long-life, and high-reliability components in high-precision industries, leading to their wide application in aerospace, weaponry, petrochemicals, and everyday life. With the continuous development of aerospace and other industrial technologies, even higher requirements are being placed on the specific strength and ductility of structural titanium alloys.

[0003] Strengthening titanium alloys by constructing dense coherent phase interfaces through martensitic transformation is a crucial method for enhancing their strength and toughness. Coherent phase interfaces effectively hinder dislocation slip, thereby improving alloy strength, but they are less prone to causing severe localized stress concentrations and premature fracture due to microcrack initiation. Compared to steel, interstitial oxygen atoms only cause a small elastic distortion of the hexagonal martensite in titanium alloys, resulting in a weaker interstitial strengthening effect. However, since martensite is metastable, it can decompose during subsequent annealing, leading to a significant strengthening effect. Simultaneously, the precipitation of martensitic phase transformation exhibits variant selection and adaptive characteristics. During precipitation, martensite is influenced by cooling rate, solution temperature, alloy composition, and crystal defects, spontaneously constructing a microstructure with a dominant orientation texture. Furthermore, many martensites interact, precipitating unique adaptive structures such as triangular, V-shaped, Z-shaped, trapezoidal, and parallel clusters. Utilizing these structures can effectively regulate the mechanical properties of the alloy. Therefore, how to fully utilize the excellent deformation characteristics brought about by martensitic phase transformation and develop and design many titanium alloys with excellent mechanical properties of "high strength and high plasticity" has become a scientific problem that the materials science community urgently needs to solve. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention provides a high-strength and high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy and its preparation method, achieving a good match between ultra-high yield strength, large tensile plasticity, and high work hardening capability.

[0005] This invention is achieved through the following technical solution:

[0006] A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, comprising, by mass percentage, 4.5-6.2% Al, 4.2-5.8% Zr, 2.2-3.2% Cr and 1.8-2.2% Cu, with the balance being Ti and unavoidable impurity elements.

[0007] Preferably, the microstructure of the Ti-Al-Zr-Cr-Cu titanium alloy is equiaxed. p A mixed structure of phase + α” / β”.

[0008] Preferably, the Ti-Al-Zr-Cr-Cu titanium alloy has a tensile strength of 1590-1149 MPa, a yield strength of 1055-1492 MPa, and a uniform elongation of 13.8%.

[0009] A method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy includes the following steps:

[0010] Step 1: Hot-roll the titanium alloy ingot sequentially in the single-phase region and the two-phase region;

[0011] Step 2: The rolled titanium alloy ingot is solution treated at a temperature below the phase transformation point in the α+β two-phase region, then quenched to room temperature, and then aged at 300-325℃ for 30 min to obtain a high-strength and high-ductility Ti-Al-Zr-Cr-Cu titanium alloy.

[0012] Preferably, the method for hot rolling in the single-phase region described in step 1 is as follows:

[0013] Titanium alloy ingots are hot rolled at 10-30°C above the phase transformation point in the two-phase region, with a deformation of 50%, and then cooled to room temperature.

[0014] Preferably, the method for hot rolling the two-phase region is as follows:

[0015] The titanium alloy ingot is hot rolled at 10-30℃ below the phase transformation point in the two-phase region, with a deformation of 35%.

[0016] Preferably, the solution treatment process is as follows:

[0017] After rolling, the titanium alloy ingot is held at 30°C below the phase transformation point in the α+β two-phase region for 1-10 minutes. The primary α precipitates in the titanium alloy microstructure exhibit elongated and equiaxed morphologies.

[0018] Preferably, the quenching is water-based quenching or oil-based quenching.

[0019] Preferably, the aging treatment is performed at a temperature of 300–325°C for 2 hours.

[0020] Preferably, the titanium alloy ingot of step 1 is prepared by air arc melting.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects:

[0022] This invention provides a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, addressing the challenges of insufficient strength and significant temper brittleness in martensitic titanium alloys, which represent a strength-ductility inversion. By introducing Cu to regulate phase stability and construct an orthorhombic martensite structure, the invention leverages the superior properties of martensitic phase transformation, such as high work hardening, grain refinement, and increased phase interface density, to achieve a synergistic improvement in strength and ductility. This invention actively adds Cu to the alloy composition, retains a large number of dislocations generated during thermomechanical processing through short-time solution treatment after rolling, and constructs martensitic microstructures with different volume fractions / sizes and adaptive structures by controlling the cooling rate (water cooling and oil cooling). Aging treatment causes partial martensite decomposition and precipitation of nanoscale Ti₂Cu particles, resulting in significant strengthening. The alloy of this invention exhibits excellent room-temperature mechanical properties, as shown in Table 1, demonstrating a clear strength-ductility advantage. More importantly, this research fully utilizes multiple strategies for controlling martensitic phase transformation, demonstrating the immense potential for exploring and utilizing martensitic phase transformation to improve the mechanical properties of alloys, and achieving a good balance between ultra-high yield strength, high tensile plasticity, and high work hardening capacity. The titanium alloy prepared by this invention possesses excellent corrosion resistance and high specific strength, making it an advantageous structural material for a wide range of industrial applications. Attached Figure Description

[0023] Figure 1 This describes the layered martensitic microstructure of the water-cooled Ti-Al-Zr-Cr-Cu titanium alloy of the present invention.

[0024] Figure 2 The present invention relates to an oil-cooled Ti-Al-Zr-Cr-Cu titanium alloy with an interlaced multi-level martensitic microstructure.

[0025] Figure 3 Tensile property curves of the Ti-Cr-Zr-Al basic alloy and the water-cooled and oil-cooled Ti-Al-Zr-Cr-Cu titanium alloys of this invention. Detailed Implementation

[0026] The present invention will now be described in further detail with reference to the accompanying drawings. These descriptions are intended to explain the invention and not to limit it.

[0027] A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, comprising, by mass percentage, 4.5-6.2% Al, 4.2-5.8% Zr, 2.2-3.2% Cr and 1.8-2.2% Cu, with the balance being Ti and unavoidable impurity elements.

[0028] The raw materials used in the alloy smelting include: high-purity titanium, high-purity aluminum, high-purity zirconium, high-purity chromium, and high-purity copper.

[0029] A method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy includes the following steps:

[0030] Step 1: Prepare Ti-Al-Zr-Cr-Cu titanium alloy ingots;

[0031] According to the composition design, appropriate raw materials were selected for alloy preparation and mixed evenly according to atomic percentages, with the weight of the raw materials accurate to 0.01g. The alloy was then melted using a vacuum arc melting method. During the melting process, a vacuum of 3Pa was first applied, followed by the introduction of high-purity argon gas and then vacuuming again. The furnace was cleaned three times to ensure a high-purity vacuum environment. The melting induction current was 450–550A, and electromagnetic stirring was used during the alloy melting process. The melting was repeated five times to ensure uniform composition. Finally, the alloy was cooled in a water-cooled copper crucible to obtain an ingot; thus, a Ti-Al-Zr-Cr-Cu titanium alloy ingot was obtained.

[0032] Step 2: Hot-roll the titanium alloy ingot in the two-phase region;

[0033] After the ingot is peeled and the riser is cut, it is hot rolled. The rolling process is divided into two steps. The rolling temperature of the first rolling is 10-30℃ higher than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 50%. After rolling, it is air-cooled. The rolling temperature of the subsequent rolling is 10-30℃ lower than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 35%.

[0034] Step 3: Solution treatment and aging treatment;

[0035] The rolled titanium alloy ingot was solution treated in the α+β two-phase region (approximately 30°C below the phase transformation point), followed by quenching to room temperature and then aging treatment to obtain a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy. The microstructure consisted of α... p It is composed of phase and nanotwinned martensite α″.

[0036] Titanium alloy ingots are quenched using either water or oil.

[0037] The alloy ingot, after water quenching, was subjected to aging treatment at 300–325℃ for 2 hours. The resulting high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy exhibited the following microstructure characteristics: Figure 1 As shown.

[0038] The alloy ingots quenched in oil were subjected to aging treatment at 300–325℃ for 2 hours. The resulting high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy exhibited the following microstructure characteristics: Figure 2 As shown.

[0039] This preparation process utilizes the numerous dislocations generated during hot rolling, followed by water and oil cooling, to mediate the formation of densely coherent nano-α″ martensite. Aging treatment further decomposes the martensite, effectively hindering dislocation slip and additional phase transformations, thus providing a strengthening effect. Simultaneously, Ti₂Cu intermetallic compounds with a size of approximately 17-25 nm precipitate in the alloy, distributed within the α″ region. p At the / β or α″ / β interface, the overall strength and plasticity of the alloy are synergistically enhanced.

[0040] Example 1

[0041] A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, comprising, by mass percentage, 5.2% Al, 4.5% Zr, 2.8% Cr and 2% Cu, with the balance being Ti and unavoidable impurities.

[0042] The preparation method of this Ti-Al-Zr-Cr-Cu titanium alloy is as follows:

[0043] Step 1: Prepare Ti-Al-Zr-Cr-Cu titanium alloy ingots;

[0044] According to the composition design, appropriate raw materials were selected for alloy preparation and mixed evenly according to atomic percentages, with the weight of the raw materials accurate to 0.01g. The alloy was then melted using a vacuum arc melting method. During the melting process, a vacuum of 3Pa was first established, followed by the introduction of high-purity argon gas and then vacuuming again. The furnace was cleaned three times to ensure a high-purity vacuum environment. The melting induction current was 450A, and electromagnetic stirring was used during the alloy melting process. The melting was repeated five times to ensure uniform composition. Finally, the alloy was cooled in a water-cooled copper crucible to obtain an ingot; thus, a Ti-Al-Zr-Cr-Cu titanium alloy ingot was obtained.

[0045] Step 2: Hot-roll the titanium alloy ingot in the two-phase region;

[0046] After the ingot is peeled and the riser is cut, it is hot rolled. The rolling process is divided into two steps. The rolling temperature of the first rolling is 10°C higher than the phase transformation point of the two-phase region, the holding time of each rolling pass is 1 minute, the deformation is 50%, and the rolling is followed by air cooling. The rolling temperature of the subsequent rolling is 10°C lower than the phase transformation point of the two-phase region, the holding time of each rolling pass is 1 minute, and the deformation is 35%.

[0047] Step 3: Solution treatment and aging treatment;

[0048] The rolled titanium alloy ingot was solution treated in the α+β two-phase region (30℃ below the phase transformation point), followed by water quenching to room temperature. The quenched alloy ingot was then aged at 300℃ for 2 hours. The resulting high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy exhibited the following microstructure characteristics: Figure 1As shown, this high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy has a microstructure consisting of α... p It is composed of phase and nanotwinned martensite α″.

[0049] The titanium alloy obtained through the above process exhibits layered α-structure. p Phase, equiaxed α p Phase and nanomartensite α″ lamellae, wherein α p The total content of the phases accounts for 23-28%. Nano-α″ martensite mostly exhibits a parallel layered structure, while the primary β phase is divided into lamellar structures by the martensite. Furthermore, the interface between the martensite and β phase is a coherent interface. Therefore, this layered mixed structure possesses extremely high strength while also exhibiting good plasticity. According to the requirements of GB / T228.1-2010 standard, the mechanical properties of the alloy were measured as follows: tensile strength R... m The yield strength is 1149 MPa, and the yield strength R is 1149 MPa. p0.2 The strength is 1055 MPa, and the uniform elongation δ / % is 15.7 ± 0.5. This alloy exhibits extremely excellent strength and ductility.

[0050] Example 2

[0051] A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, comprising, by mass percentage, 4.5% Al, 4.2% Zr, 2.2% Cr and 1.8% Cu, with the balance being Ti and unavoidable impurities.

[0052] The preparation method of this Ti-Al-Zr-Cr-Cu titanium alloy is as follows:

[0053] Step 1: Prepare Ti-Al-Zr-Cr-Cu titanium alloy ingots;

[0054] According to the composition design, appropriate raw materials were selected for alloy preparation and mixed evenly according to atomic percentages, with the weight of the raw materials accurate to 0.01g. The alloy was then melted using a vacuum arc melting method. During the melting process, a vacuum of 3Pa was first established, followed by the introduction of high-purity argon gas and then vacuuming again. The furnace was cleaned three times to ensure a high-purity vacuum environment. The melting induction current was 500A, and electromagnetic stirring was used during the alloy melting process. The melting was repeated five times to ensure uniform composition. Finally, the alloy was cooled in a water-cooled copper crucible to obtain an ingot; thus, a Ti-Al-Zr-Cr-Cu titanium alloy ingot was obtained.

[0055] Step 2: Hot-roll the titanium alloy ingot in the two-phase region;

[0056] After peeling and cutting the risers, the ingot is hot-rolled in two steps. The rolling temperature of the first rolling is 20°C higher than the phase transformation point of the two-phase region, the holding time for each rolling pass is 1 minute, and the deformation is 50%. After rolling, it is air-cooled. The rolling temperature of the subsequent rolling is 15°C lower than the phase transformation point of the two-phase region, the holding time for each rolling pass is 1 minute, and the deformation is 35%.

[0057] Step 3: Solution treatment and aging treatment;

[0058] The rolled titanium alloy ingot was solution treated in the α+β two-phase region (approximately 30°C below the phase transformation point), followed by water quenching to room temperature. The quenched ingot was then aged at 325°C for 2 hours to obtain a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy. The microstructure of this high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy consists of α... p It is composed of phase and nanotwinned martensite α″.

[0059] The microstructure of the high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy obtained in this embodiment is similar to that of Example 1. The mechanical properties of the alloy were measured according to the requirements of GB / T228.1-2010 standard as follows: tensile strength R... m The yield strength is 1340 MPa, and the yield strength R is 1340 MPa. p0.2 The strength is 1265 MPa, and the uniform elongation δ / % is 16.2 ± 0.5. This alloy exhibits extremely excellent strength and ductility.

[0060] Example 3

[0061] A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, comprising, by mass percentage, 6.2% Al, 5.8% Zr, 3.2% Cr and 2.2% Cu, with the balance being Ti and unavoidable impurities.

[0062] The preparation method of this Ti-Al-Zr-Cr-Cu titanium alloy is as follows:

[0063] Step 1: Prepare Ti-Al-Zr-Cr-Cu titanium alloy ingots;

[0064] According to the composition design, appropriate raw materials were selected for alloy preparation and mixed evenly according to atomic percentages, with the weight of the raw materials accurate to 0.01g. The alloy was then melted using a vacuum arc melting method. During the melting process, a vacuum of 3Pa was first established, followed by the introduction of high-purity argon gas and then vacuuming again. The furnace was cleaned three times to ensure a high-purity vacuum environment. The melting induction current was 550A, and electromagnetic stirring was used during the alloy melting process. The melting was repeated five times to ensure uniform composition. Finally, the alloy was cooled in a water-cooled copper crucible to obtain an ingot; thus, a Ti-Al-Zr-Cr-Cu titanium alloy ingot was obtained.

[0065] Step 2: Hot-roll the titanium alloy ingot in the two-phase region;

[0066] After the ingot is peeled and the riser is cut, it is hot rolled. The rolling process is divided into two steps. The rolling temperature of the first rolling is 30°C higher than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 50%. After rolling, it is air-cooled. The rolling temperature of the subsequent rolling is 30°C lower than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 35%.

[0067] Step 3: Solution treatment and aging treatment;

[0068] The rolled titanium alloy ingot was solution treated in the α+β two-phase region (approximately 30°C below the phase transformation point), followed by oil quenching to room temperature. The quenched alloy ingot was then aged at 310°C for 2 hours. The resulting high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy exhibited the following microstructure characteristics: Figure 2 As shown, this high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy has a microstructure consisting of α... p It consists of a phase and dense nanotwinned martensite α″.

[0069] The titanium alloy obtained through the above process exhibits layered α-structure. p Phase, equiaxed α p Phase and nanomartensite α″ lamellae, wherein α p The total content of the phase is 24-30%. Nano-α″ martensite exhibits a mixed multi-level structure composed of coarse laths and fine layers. The primary β phase is divided into very fine lamellar structures by the martensite, such as... Figure 2 As shown. Furthermore, the interface between martensite and β is a coherent interface, while the interfaces between martensite are semi-coherent. Therefore, this hierarchical, mixed structure possesses extremely high strength. According to the requirements of GB / T228.1-2010 standard, the mechanical properties of the alloy were measured as follows: tensile strength R... m The yield strength is 1470 MPa, and the yield strength R is... p0.2 The strength is 1397 MPa, and the uniform elongation δ / % is 10.7 ± 0.5. This alloy exhibits extremely excellent strength and ductility.

[0070] Example 4

[0071] A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, comprising, by mass percentage, 4.2% Al, 4.5% Zr, 4.2% Cr and 2.2% Cu, with the balance being Ti and unavoidable impurities.

[0072] The preparation method of this Ti-Al-Zr-Cr-Cu titanium alloy is as follows:

[0073] Step 1: Prepare Ti-Al-Zr-Cr-Cu titanium alloy ingots;

[0074] According to the composition design, appropriate raw materials were selected for alloy preparation and mixed evenly according to atomic percentages, with the weight of the raw materials accurate to 0.01g. The alloy was then melted using a vacuum arc melting method. During the melting process, a vacuum of 3Pa was first established, followed by the introduction of high-purity argon gas and then vacuuming again. The furnace was cleaned three times to ensure a high-purity vacuum environment. The melting induction current was 480A, and electromagnetic stirring was used during the alloy melting process. The melting was repeated five times to ensure uniform composition. Finally, the alloy was cooled in a water-cooled copper crucible to obtain an ingot; thus, a Ti-Al-Zr-Cr-Cu titanium alloy ingot was obtained.

[0075] Step 2: Hot-roll the titanium alloy ingot in the two-phase region;

[0076] After the ingot is peeled and the riser is cut, it is hot rolled. The rolling process is divided into two steps. The rolling temperature of the first rolling is 30°C higher than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 50%. After rolling, it is air-cooled. The rolling temperature of the subsequent rolling is 25°C lower than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 35%.

[0077] Step 3: Solution treatment and aging treatment;

[0078] The rolled titanium alloy ingot was solution treated in the α+β two-phase region (approximately 30°C below the phase transformation point), followed by oil quenching to room temperature. The quenched ingot was then aged at 320°C for 2 hours to obtain a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy. The microstructure of this high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy consists of α... p It consists of a phase and dense nanotwinned martensite α″.

[0079] The microstructure of the high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy obtained by aging the alloy ingot after oil quenching is as follows: Figure 2 As shown. At this point, the martensitic decomposition phenomenon is more intense. This layered, mixed structure, after decomposition, possesses extremely high strength. According to the requirements of GB / T228.1-2010 standard, the mechanical properties of the alloy are as follows: Tensile strength R... m The yield strength is 1590 MPa, and the yield strength R is... p0.2 The strength is 1492 MPa, and the uniform elongation δ / % is 4.64 ± 0.5. This alloy exhibits extremely excellent strength and ductility.

[0080] Comparative Example 1

[0081] In this comparative example, the titanium alloy composition does not contain Cu atoms.

[0082] A Ti-Al-Zr-Cr titanium alloy, by mass percentage comprising 5.2% Al, 4.5% Zr and 2.8% Cr, with the balance being Ti and unavoidable impurities.

[0083] The preparation method of this Ti-Al-Zr-Cr titanium alloy is as follows:

[0084] Step 1: Prepare Ti-Al-Zr-Cr-Cu titanium alloy ingots;

[0085] According to the composition design, appropriate raw materials were selected for alloy preparation and mixed evenly according to atomic percentages, with the weight of the raw materials accurate to 0.01g. The alloy was then melted using a vacuum arc melting method. During the melting process, a vacuum of 3Pa was first applied, followed by the introduction of high-purity argon gas and then vacuuming again. The furnace was cleaned three times to ensure a high-purity vacuum environment. The melting induction current was 450–550A, and electromagnetic stirring was used during the alloy melting process. The melting was repeated five times to ensure uniform composition. Finally, the alloy was cooled in a water-cooled copper crucible to obtain an ingot; thus, a Ti-Al-Zr-Cr-Cu titanium alloy ingot was obtained.

[0086] Step 2: Hot-roll the titanium alloy ingot in the two-phase region;

[0087] After the ingot is peeled and the riser is cut, it is hot rolled. The rolling process is divided into two steps. The rolling temperature of the first rolling is 10-30℃ higher than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 50%. After rolling, it is air-cooled. The rolling temperature of the subsequent rolling is 10-30℃ lower than the phase transformation point of the two-phase region. The holding time for each rolling pass is 1 minute, and the deformation is 35%.

[0088] Step 3: Solution treatment and aging treatment;

[0089] The rolled titanium alloy ingot was solution treated in the α+β two-phase region (approximately 30°C below the phase transformation point), followed by water quenching to room temperature to obtain a high-strength, high-ductility martensitic Ti-Al-Zr-Cr titanium alloy. The microstructure consisted of α... p The alloy is composed of phase and nanotwinned martensite α″. The quenched alloy ingot was subjected to aging treatment at 300℃ for 2 hours. Due to the lack of Cu strengthening, the alloy has low strength. According to GB / T228.1-2010 standard, the mechanical properties of the alloy were measured as follows: tensile strength R... m The yield strength is 1092 MPa, and the yield strength R is 1092 MPa. p0.2 The strength is 950 MPa, and the uniform elongation δ / % is 19.8 ± 1.5.

[0090] Figure 1 This describes the layered martensitic microstructure of the water-cooled Ti-Al-Zr-Cr-Cu titanium alloy of this invention. (a) shows the α-structure. pPhase and β trans (a) Scanned images of the tissue; (b) Size and aspect ratio distribution of αp; (c) β trans (d) is the bright field image of the tissue; (c) is the dark field image corresponding to (c), where the layered parallel martensite structure can be seen.

[0091] Figure 2 The microstructure of the oil-cooled Ti-Al-Zr-Cr-Cu titanium alloy of this invention is an interlaced multi-level martensitic structure. (a) is α p Phase and β trans (a) is a scanned image of the tissue; (b) is α p Size and aspect ratio distribution; (c) is β trans (d) is the bright field image of the organization; (c) is the dark field image corresponding to (c), where the staggered martensite structure can be seen.

[0092] Figure 3 The tensile property curves of four embodiments, namely the Ti-Cr-Zr-Al basic alloy and the water-cooled or oil-cooled Ti-Al-Zr-Cr-Cu titanium alloy of the present invention, demonstrate an excellent balance between strength and plasticity.

[0093] The method for preparing Ti-Al-Zr-Cr-Cu titanium alloy provided by this invention involves hot rolling / short-time solution treatment and aging treatment in the transphase region of a titanium alloy ingot to obtain a high-strength and high-ductility Ti-Al-Zr-Cr-Cu titanium alloy. This Ti-Al-Zr-Cr-Cu titanium alloy comprises 4.7-6% Al, 4.0-5.0% Zr, 2.0-3.5% Cr, 1.8-2.2% Cu, with the balance being Ti and unavoidable impurity elements. By adding Cu to adjust phase stability, the formation of dense, coherent nanomartensite α″ is mediated and partially decomposed during aging, and nanoscale Ti₂Cu particles precipitate in the microstructure, thereby improving the strength and ductility of the titanium alloy. The Ti-Al-Zr-Cr-Cu titanium alloy of this invention achieves high yield strength (~1.40 GPa), ultimate tensile strength (~1.50 GPa), and high uniform ductility (~10.7%), exhibiting excellent mechanical properties. This high strength and mechanical property originates from the partial decomposition of nanomartensite and the precipitation of Ti-Cu intermetallic compounds. The martensite precipitation is controlled by adjusting the processing parameters, thereby achieving both high yield strength and high ductility. This invention achieves the goal of triggering a sustained and self-hardening deformation mechanism of martensite while ensuring a certain level of plasticity through the coordination of coherent phase interfaces. The alloy of this invention exhibits excellent room-temperature mechanical properties. By adjusting the cooling rate and aging temperature, the precipitation and decomposition of martensite can be effectively controlled, thereby obtaining different strength-plasticity balances. Compared with currently reported titanium alloys, its mechanical properties show a significant advantage in strength and plasticity. More importantly, this research fully utilizes multiple strategies for controlling martensitic phase transformation, demonstrating a great potential for exploring and utilizing martensitic phase transformation to improve the mechanical properties of alloys, and achieving a good balance between ultra-high yield strength, high tensile plasticity, and high work hardening capability.

[0094] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy, characterized in that, It contains, by mass percentage, 4.5-6.2% Al, 4.2-5.8% Zr, 2.2-3.2% Cr and 1.8-2.2% Cu, with the balance being Ti and unavoidable impurity elements.

2. The high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 1, characterized in that, The microstructure of the Ti-Al-Zr-Cr-Cu titanium alloy is characterized by "equiaxed α". p A mixed structure of phase + α” / β”.

3. The high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 1, characterized in that, The Ti-Al-Zr-Cr-Cu titanium alloy has a tensile strength of 1590-1149 MPa, a yield strength of 1055-1492 MPa, and a uniform elongation of 13.8%.

4. A method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Hot-roll the titanium alloy ingot sequentially in the single-phase region and the two-phase region; Step 2: The rolled titanium alloy ingot is solution treated at a temperature below the phase transformation point in the α+β two-phase region, then quenched to room temperature, and then aged at 300-325℃ for 30 min to obtain a high-strength and high-ductility Ti-Al-Zr-Cr-Cu titanium alloy.

5. The method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 4, characterized in that, The method for hot rolling in the single-phase region described in step 1 is as follows: The titanium alloy ingot is hot-rolled 10-30°C above the phase transformation point in the two-phase region, with a deformation of 50%, and then cooled to room temperature.

6. The method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 4, characterized in that, The method for hot rolling in the two-phase region is as follows: The titanium alloy ingot is hot rolled at 10-30℃ below the phase transformation point in the two-phase region, with a deformation of 35%.

7. The method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 4, characterized in that, The solution treatment process is as follows: After rolling, the titanium alloy ingot is held at 30°C for 1-10 minutes below the phase transformation point in the α+β two-phase region. The primary α precipitates in the titanium alloy microstructure exhibit elongated and equiaxed morphologies.

8. The method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 4, characterized in that, The quenching is water-based quenching or oil-based quenching.

9. The method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 4, characterized in that, The aging treatment is performed at a temperature of 300-325℃ for 2 hours.

10. The method for preparing a high-strength, high-ductility martensitic Ti-Al-Zr-Cr-Cu titanium alloy according to claim 4, characterized in that, The titanium alloy ingot of step 1 was prepared by air arc melting.